The electrochemical reactions of pyridoxine (vitamin B6) and some phenolic compounds in aprotic organic solvents - Lee, Jazreen Hui Qi (2017)
Phenols are invaluable structural units found in a wide range of natural and artificial compounds, and have been used for numerous applications that are necessary for our daily lives. As a result, this has led to many remarkable papers on the voltammetric studies of this class of compounds. In this thesis, the detailed redox chemistry of four phenolic and phenolic-type compounds, sesamol, vanillin, diethylstilbestrol (DES) and pyridoxine (PN) were investigated in acetonitrile solutions. As the four aforementioned compounds are food and/or food-related molecules, examination on the electrochemical pathways of these chemicals can provide information such as the number of electrons involved and the identities of the associated intermediates that may be useful in obtaining insights into the metabolic pathways partaken by these four molecules in the biological system and possibly relate to some of their proposed biological functions such as antioxidant properties. In addition, an aprotic organic solvent (acetonitrile) was used in this work since a search of literature reveals that majority of the electrochemical accounts of these compounds are documented in protic and/or aqueous media, with reports focusing on the aprotic system remaining less well-developed. By means of a combination of various electrochemical techniques such as cyclic voltammetry and controlled potential electrolysis, and consistent with the behavior of a typical phenol, the compounds were generally found to undergo an electrochemical oxidation reaction, with some also exhibiting reduction phenomena. Using the electrochemical responses gathered, identities of the intermediates and products involved together with their mechanistic pathways were proposed. In addition, it is worthwhile to highlight that phenols (e.g. the essential micronutrient vitamin E, α-tocopherol) have been demonstrated to be highly sensitive to the presence of trace amounts of moisture, such as by actively participating in hydrogen bonding interactions. As such, the effect of low levels of water on the electrochemical behavior of the aforementioned compounds were also examined. In particular, the voltammetric profiles of sesamol and vanillin were found to be affected by the presence of moisture, whereby their respective oxidation peak potentials were generally found to shift towards more negative potentials as the water content was increased.